Aesthetics and Asceticism in Inca Religion - Classen, Constance (Anthropologica, 2022)
Among the Incas, sensory experience served as both a marker of status and a conduit to the supernatural. Ritual was preceded by a deprivation of sensation, especially taste, and followed by the consumption of highly flavoured food. Special sensory powers were ascribed to diviners and ceremonial virgins, with odours being especially associated with the latter role. Both intensive discipline and exquisite sensation were valued and formed part of the training and perquisites of the élite.